Sibling Gender, Inheritance Customs and Educational Attainment: Evidence from Matrilineal and Patrilineal Societies - Matthew Collins (Lund University, School of Economics and Management, Department of Economics, 2022)
Using data from 27 sub-Saharan African countries, I identify the causal effect of sibling gender on education and how it varies according to inheritance customs. Boys who inherit their father's property experience no effect of sibling gender, while boys who do not inherit experience a significant negative effect of having a brother. Having a brother has a small negative effect on the education of girls, regardless of inheritance customs. The effect of sibling gender converges after the introduction of laws guaranteeing that children inherit from their parents, suggesting that parents substitute between transferring inheritance and investing in their children's education.
Keywords: D13; I20; J16; 330; sibling gender; patriliny; matriliny; educational attainment